Understanding taxation law 2014 - Gilders, F.M. (Frank M.); Taylor, C. J. (Christopher John), 1952-; Walpole, Michael, 1959-; Burton, Mark; Ciro, Tony (Chatswood, NSW : LexisNexis Butterworths, 2014)
An annual taxation law text for business, accounting and law students focusing on the fundamental concepts of taxation law while using a pedagogical structure to assist learning.
First edition 2002.
Previous edition 2013.
Reprinted 2005, 2006 and 2008.
Includes bibliographical references and index.
Keywords: Taxation -- Law and legislation -- Australia; Income tax -- Law and legislation -- Australia; Australian